Pengembangan Aplikasi Catatan Keuangan Untuk Usaha Mikro Kecil Menengah (UMKM) Berbasis Flutter - Fafions Osama Effendy; Moh. Noor Al Azam; Rr. Prastoeti (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
This paper aims to overcome the problem of manual financial recording that is still commonly used by MSMEs, which often causes data loss and inefficiency in financial management. To answer this challenge, researchers developed a mobile-based financial recording application using Flutter and a number of available supporting packages. This application is designed to be able to record and store income and expenditure data directly on the user's mobile device, making it easier for MSMEs to monitor their financial condition in real time. The development was carried out using a waterfall model approach, which includes the stages of analysis, design, implementation, and testing. To test the functional performance of the application, the Black Box testing method is used to assess the accuracy and reliability of the features without looking at the internal code structure. The test results show that all features can function as they should and the application is considered effective in supporting digital MSME financial recording.